PEREMPUAN DALAM PUISI CINTA SHUNTARO TANIKAWA DAN W.S. RENDRA: Sebuah Kajian Sastra Bandingan1 - Damayanti, Silvia (Universitas Papua Manokwari, 2016)
Women are the most interesting objects to be used as a discussing subject, research topics, or a source of inspiration for the author in the field of arts and literature. However, there is a phenomenon which is inversely proportional to that, in everyday life, in a society, that embraces patriarchal system, which is women are often ignored, diminished, even considered unimportant. The phenomenon experienced by the women also occurs in Indonesian and Japanese society that embrace patriarchal system.Â Speaking about the position of women as a reflection of society in Indonesia and Japan can be seen through literature, as in poetry. One genre of literature that contains the overflow of feelings, imagination, and the poetâs mind cannot be separated from the part of the community. Indeed, the creation of a poem was influenced by the environment where the poet was born and lived. Therefore, throughout the poetry, the ideology of community where the poets came can be revealed, especially in comparing the love poetry from the two countries. The objects of the study are love poetries by WS Rendra and Shuntaro Tanikawa. This study uses the comparative method, the approach of comparative literature, and feminist theory. Throughout the study of comparative literature between WS Rendra and Shuntaro Tanikawaâs love poetries, it is expected that the public would know the position of women in the view of the poet in Indonesia and Japan society.Â